A Brief Introduction to Recent Chinese Studies on Sanskrit and Khotanese (Chiefly Buddhist) Literature - Silk, Jonathan A. (Indo-Iranian journal, 2021)
Abstract The past decade has seen the appearance of a number of Chinese publications relevant to the readership of the Indo-Iranian Journal . This article briefly introduces some of those publications, dealing mostly with Buddhist sources, primarily in Sanskrit, Khotanese and Middle Indic.